A rare presentation of stiff-person syndrome with a nonspecific focal myositis: A case report - Arij Ezzouhour Yahyaoui; Sameh Sayhi; Nour Elhouda Guediche; Zakaria Saied; Bilel Arfaoui; Faida Ajili; Ines Bedoui; Samia Ben Sassi; Nadia Ben Abdelhafidh (Romanian Journal of Rheumatology)
Introduction. The stiff-person syndrome (SPS) is a rare disease whose incidence is estimated at approximately 1 in a million individuals in the general population. Diagnosis relies on a combination of clinical, immunological, and electromyographic items. We present the case of a patient diagnosed with the idiopathic SPS, initially misdiagnosed as focal paravertebral myositis. Case presentation. A 36-year-old patient was referred to us for the investigation of subacute dorsal myalgias. The patient reported a severe torticollis seven months ago, which resolved spontaneously after one month, and some episodes of back stiffness. On examination, the patient was afebrile, had hyperlordosis with a paravertebral contracture and tenderness. Neurological and cognitive examinations were normal. C-reactive Protein was at 137 mg/l. The rest of laboratory investigations, including creatine phosphokinase (CPK), were within normal range. Spinal MRI revealed T2 hyperintensity in the semispinalis muscle, erector spinae muscle, trapezius muscle, as well as the intervertebral muscles. Therefore, focal paravertebral myositis was suspected. The electromyogram (EMG) revealed the presence of a continuous motor unit activity in agonist and antagonist muscles, suggestive of stiff-person syndrome. Antinuclear antibodies, anti-glutamic acid decarboxylase 65 and onconeuronal antibodies were negative. Analysis of the cerebrospinal fluid, including anti-glutamic acid decarboxylase 65 test, was normal. We noticed that the paravertebral contracture became less noticeable when the patient was commenced on diazepam. Diagnosis of SPS was established according to Dalakas criteria. Investigations for an underlying neoplasm, were normal. Associated autoimmune disorders have been ruled out. The MRI description was rather explained by the continuous contraction of the affected muscles. Treatment included diazepam, baclofen, intravenous immunoglobulin and corticosteroids. The patient showed important signs of improvement. Conclusion. SPS is a rare condition whose diagnosis can be delayed. Recognizing and managing SPS as early as possible is crucial. It is based on clinical reasoning, imaging, biological features and EMG.